Functional and radiological correlation in surgically managed severe supracondylar humerus fracture in a pediatric cohort using pediatric outcomes data collection instrument upper extremity scale: A report from a level V trauma center in rural Central India - Deeptiman James; Manjulata Gajendran; Tapan Kumar Paraseth (Wolters Kluwer Medknow Publications, 2017)
Context: This study highlights the correlation between functional and radiological outcome in a pediatric cohort who were surgically managed for displaced supracondylar humerus fractures at a level V trauma center. Settings: Surgically managed pediatric Gartland type III supracondylar humerus fracture patients were retrospectively assessed. All patients were managed at the level V trauma center from 2011 to 2015. Patients with regular follow-up were included in the study. Methodology: Baumann's angle and pediatric outcomes data collection instrument (PODCI) upper extremity and physical function core scale administered at 6 months follow-up were used to assess the radiological and functional outcomes. Results: Thirty-seven children with supracondylar humerus fracture were treated at our center. Fifteen patients underwent surgical management for Gartland type III fracture. One patient presented with open fracture. Three patients with delayed presentation underwent open reduction and K-wire fixation. Ten patients underwent closed reduction under fluoroscopy guidance and K-wire fixation. Fourteen patients were followed up for 6 months and underwent radiological evaluation and functional assessment. One patient was lost to follow-up. Two patients had median nerve palsy, one patient had complete recovery at 6 months follow-up, and the other patient had partial recovery. Average Baumann's angle was 72.97΀ (standard deviation [SD] =8.5), ranging from 57.8΀ to 84.86΀. The average PODCI outcome was 50.5 (SD = 6.16), ranging from 36 to 57. A weak Pearson's correlation coefficient (r = 0.476) was observed between radiological and functional outcomes. Conclusions: Satisfactory outcomes were observed in most patients who underwent surgical management of severe Gartland type III supracondylar fracture. Low PODCI score was observed with partial median nerve recovery. A weak linear correlation between Baumann's angle and PODCI score suggests multifactorial determinants of functional outcomes in pediatric supracondylar fracture.